2007
DOI: 10.1111/j.1600-0528.2006.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between routine visits for dental checkup and self‐perceived oral health in an adult population in Rio de Janeiro: the Pró‐Saúde Study

Abstract: Not visiting the dentist for a routine dental check increased the chance of reporting one's own oral health as bad. In any case, the habit of visiting for dental 'checkup, once per year or once every 2 years was associated with nearly all the individuals perceiving his/her oral health positively. However, in order to gather more solid scientific data to guide public policies it is necessary to perform longitudinal studies, especially experiments in different populations focused mainly on the socioeconomic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
3
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 40 publications
9
59
3
21
Order By: Relevance
“…No presente estudo, não houve associação entre a autoavaliação negativa da saúde bucal com as variáveis relacionadas à utilização de serviços odontológicos. No entanto, AfonsoSouza et al 24 encontraram associação entre uma autoavaliação mais positiva da saúde bucal e o uso regular de serviços odontológicos. Na tentativa de explicar tal associação, os autores sugeriram duas hipóteses: que a autoavaliação positiva seria consequência de um bom tratamento, da maior oportunidade de receber tratamentos preventivos com reflexos positivos nas condições clínicas de saúde bucal; por outro lado, essa associação estaria relacionada à ocorrência de um bem-estar psicológico associado ao cuidado com a saúde.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No presente estudo, não houve associação entre a autoavaliação negativa da saúde bucal com as variáveis relacionadas à utilização de serviços odontológicos. No entanto, AfonsoSouza et al 24 encontraram associação entre uma autoavaliação mais positiva da saúde bucal e o uso regular de serviços odontológicos. Na tentativa de explicar tal associação, os autores sugeriram duas hipóteses: que a autoavaliação positiva seria consequência de um bom tratamento, da maior oportunidade de receber tratamentos preventivos com reflexos positivos nas condições clínicas de saúde bucal; por outro lado, essa associação estaria relacionada à ocorrência de um bem-estar psicológico associado ao cuidado com a saúde.…”
Section: Resultsunclassified
“…De fato, Afonso-Souza et al 24 afirmaram, com base nos achados de seu estudo, que a manutenção da dentição natural em condição satisfatória está associada com uma melhor autoavaliação da saúde bucal, e que a ausência de dentes naturais aumentava em quatro vezes a chance de classificar sua saúde bucal como ruim.…”
Section: Resultsunclassified
“…Moreover, dental visits might reassure and inform people, boosting their confidence regarding their oral health condition, rendering them more likely to report the positive aspects of their oral health. 24 Elderly people who used public dental services showed a higher prevalence of poor SROA. In Brazil, historically, this group did not receive public dental care service, except in cases of urgency, resulting in dental mutilation.…”
Section: Discussionmentioning
confidence: 98%
“…This study examined the oral health status only of the subjects who received a workplace oral health examination, and that of subjects who did not receive such an examination remains uncertain. A previous study has found that subjects who do not visit a dentist for routine checkups have poor self-perceived oral health 20) . There is a possibility that the subjects who did not receive a workplace oral health examination and regular dental checkups in clinics might have had a poorer oral health status.…”
Section: Discussionmentioning
confidence: 99%